Influence of Water Contamination, Iron Particles, and Energy Input on the NVH Behavior of Wet Clutches - Wirkner, Johannes; Baese, Mirjam; Lebel, Astrid; Pflaum, Hermann; Völkel, Katharina; Pointner-Gabriel, Lukas; Besser, Charlotte; Schneider, Thomas; Stahl, Karsten (Lubricants, 2023)
The driving comfort and safety of the automotive powertrain are significantly related to the performance, lifetime, and functionality of the lubricant. The presented study focuses on investigating the performance loss of the lubricant due to water contamination resulting from environmental influences and iron particles originating from the wear of different machine elements. The main purpose is to determine critical factors that contribute to the degradation of the lubricant, and increase the tendency to NVH behavior, leading to adverse comfort losses to the respective user. Therefore, this performance loss is evaluated by test rig-based analysis of the friction behavior of wet clutches. Due to physical adsorption, a significant impact of water and iron contamination on the degradation of the lubricant is found, while the influence of the energy input is secondary.
CRIS-Team Scopus Importer:2025-05-19
Keywords: additives; energy input; friction behavior; ICP-OES; iron particles; lubrication; NVH; shudder; water contamination; wet clutch